Penerapan metode demonstrasi pada mata pelajaran sejarah kebudayaan islam dengan media Lumen5 di kelas VIII MTS Integral Luqman Al-Hakim Bojonegoro - Ayunda, Rina Dwi (Maliki Interdisciplinary Journal, 2025)
This article discusses the application of the demonstration method in Islamic Cultural History lessons using video-based digital media, namely Lumen5, in the eighth grade at Mts Integral Luqman Al-Hakim Bojonegoro. Islamic Cultural History lessons are known to have dense reading material, containing many names of figures, historical events, and foreign terms that are sometimes difficult for students to understand when delivered conventionally. Therefore, the demonstration method was chosen because it can present material concretely through demonstrations, making it easier for students to build visual and contextual understanding. Meanwhile, Lumen5 is used as an auxiliary medium that allows teachers to create engaging, dynamic, and interactive educational videos without requiring complex video editing skills. This study uses a qualitative descriptive approach with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the integration of the demonstration method and Lumen5 media has a positive impact on increasing students' motivation, enthusiasm, and understanding of the material being taught. Additionally, students demonstrated high learning interest and active engagement in the success of this method, including teacher professionalism, availability of technological facilities, and parental support. However, there were also some challenges faced, such as low learning interest among some students, limited learning time, and insufficient access to technological devices for all students.